ANALISIS MANAJEMEN PERPUSTAKAAN BERDASARKAN PERATURAN NO. 24 TAHUN 2007 OLEH MENTERI PENDIDIKAN NASIONAL (Studi Kasus di MAN Pekalongan) - Tria Ratnasari; Dian Nur Muniroh (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2023)
Today the development of the era makes the world of education vying to improve quality. One way is to carry out good management and improvement in the context of fulfilling the facilities and infrastructure. As well as supporting facilities and infrastructure in the educational institution. For this reason, the government through Regulation of the Minister of National Education No. 24 of 2007 sets the standard for infrastructure in an educational institution.With this regulation, the government hopes that every school will be able to manage and provide facilities and infrastructure in accordance with the guidelines listed. In the discussion the title was appointed, namely